2009
DOI: 10.1029/2008jb005831
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of micrometeorites

Abstract: [1] Most micrometeorites are strongly magnetic: the signal of a single micrometeorite may exceed the signal of a weakly magnetized standard sediment sample. Micrometeorites contain abundant magnetite, mostly produced by high-temperature oxidation during atmospheric entry. In this study, we carried out measurements on 520 micrometeorites (505 melted cosmic spherules, 6 partially melted scoriaceous micrometeorites, and 9 unmelted micrometeorites). The natural remanent magnetization and the saturation isothermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…8d). Suavet et al (2009) demonstrated that fine-grained magnetite in cosmic spherules and unmelted micrometeorites of extraterrestrial origin has potential contribution to the remanent magnetization of sediments of open ocean. We interpret these observations to show that single-domain magnetite observed from the Ajiro cherts is inferred to be the magnetic carrier of secondary component B, which is explained based on the relaxation time-blocking temperature relations for single-domain magnetite.…”
Section: Widespread Remagnetizations Recorded In Cherts Of Southwest mentioning
confidence: 99%
“…8d). Suavet et al (2009) demonstrated that fine-grained magnetite in cosmic spherules and unmelted micrometeorites of extraterrestrial origin has potential contribution to the remanent magnetization of sediments of open ocean. We interpret these observations to show that single-domain magnetite observed from the Ajiro cherts is inferred to be the magnetic carrier of secondary component B, which is explained based on the relaxation time-blocking temperature relations for single-domain magnetite.…”
Section: Widespread Remagnetizations Recorded In Cherts Of Southwest mentioning
confidence: 99%
“…Magnetite is the only significant ferromagnetic mineral in melted micrometeorites (Suavet et al, 2009b), except for occasional metal beads ($50% of cosmic spherules contain metal or sulfide beads; Taylor et al, 2009). Therefore, the value of the saturation magnetization M s is directly proportional to the amount of magnetite in the micrometeorite.…”
Section: Magnetic Propertiesmentioning
confidence: 98%
“…The magnetite wt.% is M s /0.92 for pure magnetite (Dunlop, 2002) The magnetite contents are in the range of 1.2-11.6 wt.% (these are maximum estimates as magnetite is substituted in micrometeorites; Suavet et al, 2009b). The magnetite grain sizes, estimated with the B cr /B c and M rs /M s ratios (Day, 1977), are in agreement with the results of Suavet et al (2009b): CC spherules have pseudosingle domain to single domain grains, PO and BO have larger grains in the pseudosingle domain range. PO spherule #45-5 has the highest magnetite content (11.6 wt.%) and the largest grain size: magnetite dendrites up to a few tens of micrometers in maximum dimension are visible on Fig.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…The saturation magnetization of sample #294 is 1000 times less than the one of pure maghemite, which confirms this estimate. It is difficult to say whether this small amount of magnetite/ maghemite is from extraterrestrial (micrometeorites contain $10% magnetite on average, e.g., Suavet et al, 2009), volcaniclastic, or authigenic material. Since we did not find cosmic spherules in the magnetic sub-fraction of sample #294 we assume that, if present, the micrometeorites may be enclosed inside the black micronodules and crusts we observed (e.g., Murray and Renard, 1891).…”
Section: Mineralogy Of the Metalliferous Sedimentsmentioning
confidence: 99%